Determining the optimal configuration for the zone routing protocol. - Pearlman, M.R (IEEE Journal on selected areas in communications)
The zone routing protocol (ZRP) is a hybrid routing protocol that proactively maintains routes within a local region of the network (which we refer to as the routing zone). Knowledge of this routing zone topology is leveraged by the ZRP to improve the efficiency of a reactive route query/reply mechanism. The ZRP can be configured for a particular network through adjustment of a single parameter, the routing zone radius. We address the issue of configuring the ZRP to provide the best performance for a particular network at any time. Previous work has demonstrated that an optimally configured ZRP operates at least as efficiently as traditional reactive flood-search or proactive distance vector/link state routing protocols (and in many cases, much more efficiently). Adaptation of the ZIP to changing network conditions requires both an understanding of how the ZRP reacts to changes in network behavior and a mechanism to allow individual nodes to identify these changes given only limited knowledge of the network behavior. We demonstrate the effects of relative node velocity, node density, network span, and user data activity on the performance of the ZRP. We then introduce two different schemes (?min searching? and ?traffic adaptive?) that allow individual nodes to identify and appropriately react to changes in network configuration, based only on information derived from the amount of received ZRP traffic. Through test-bed simulation, we demonstrate that these radius estimation techniques can allow the ZRP to operate within 2% of the control traffic resulting from perfect radius estimation